I heart you, you haunt me - Schroeder, Lisa (Simon Pulse, 2008)
A verse novel in which fifteen-year-old Ava, feeling guilty over the role she believes she played in her boyfriend Jackson's death, experiences a whole new range of emotions when she realizes he is back from the dead.